Influência da temperatura de calcinação do fosfogesso no desempenho de cimentos supersulfatados - Gracioli, Bruna (2016)
The supersulfated cement (CSS) basically consist of up to 90% blast furnace slag, 10-20% of a source of calcium sulfate and a small amount of alkali activator, covered by European standard EN 15743/2010. Because of this SSC are considered "green cement" low environmental impact. The source of calcium sulfate used in the preparation of CSS can be obtained from natural sources, such as gypsum or from alternative sources (industrial products), such as phosphogypsum. The phosphogypsum is a by-product of the fertilizer industry, used in the production of phosphoric acid. In this process the phosphate rock is treated with sulfuric acid to give as the major product phosphoric acid (H3PO4), gypsum and a small amount of hydrofluoric acid. The chemical composition of gypsum is basically calcium sulfate dihydrate (CaSO4.2H2O), similar to gypsum, because it can be used in this type of cement. To become anhydrous, the calcination of gypsum is necessary. The availability of the source of calcium sulfate to react with the slag is dependent on its solubility that is directly related to its calcination temperature. The solubility of the anhydrous gypsum decreases with increasing calcination temperature. This study investigated the influence of temperature of calcination of phosphogypsum on the performance of CSS. Samples were prepared with 10 and 20% of phosphogypsum calcinated at 350 to 650 ° C using KOH as an alkaline activator at three different concentrations (0.2, 0.5 and 0.8%). The results showed that all mortars presented the minimum values required by EN 15743/2010 for 7 and 28 days of hydration. In general CSS containing 10% phosphogypsum showed slightly better compressive strength results using a lower calcination temperature (350 °C) and curing all ages. The CSS containing 20% of calcined gypsum at 650 °C exhibit satisfactory compressive strenght at 28 days of hydration, but at later ages (56 to 90 days) it strongly reduced. This indicates that the calcination temperature of phosphogypsum has a strong influence on the performance of the CSS.